Applied Behavior Analysis as Treatment for Autism Spectrum Disorders: Topic Modeling and Linguistic Analysis of Reddit Posts - Bellon-Harn, Monica L.; Boyd, Ryan L.; Manchaiah, Vinaya (Frontiers in Rehabilitation Sciences, 2022)
Background: It is critical for professionals to understand the discourse landscape within various online and social media outlets in order to support families of children with autism in treatment decision making. This need is heightened when considering treatments that have garnered excitement and controversy, such as applied behavioral analysis therapy (ABA). Method: The specific aims of this study were to identify the main themes in Reddit posts about ABA-based interventions for autism using topic modelling, to examine the linguistic aspects of Reddit conversations using the LIWC analysis, and to examine the relationship between linguistic aspects and user category (i.e., pro- versus anti-ABA versus undecided, parent versus professional versus individual with autism). Results: The topic modelling resulted in 11 themes that ranged across various elements including autism as a condition and its management, stakeholders, and consequences of autism and the support needed. The individuals posting were focused on personal experiences and opinions as opposed to clinical and research information sharing. Linguistic analysis indicated that the posts reveal an intimate stance rather than an empirical stance. s Conclusions: Results provide insight into perspectives of ABA. This type of research may help in developing and distributing appropriate and evidence-based information.